The Impact of the New Production of Knowledge on Modern Universities - Grandić B. Radovan; Bosanac M. Maja (University of Belgrade, Teacher Education Faculty, 2019)
Contemporary universities, primarily conditioned by the process of globalization, are increasingly facing numerous internal and external challenges. In this context, it has become very important to explore the relationship between theory and practice, teaching and research (first and second university missions), as well as the university-community relations (third university mission). In different periods, depending on social needs, this relationship also varied and importance was attached to different missions. Based on the studied literature, the aim of this paper is to present different models of knowledge production, the so-called Model 1 and Model 2, as well as the increasing actualization of Model 3, with a special emphasis on the relationship between universities and society. The main goal has been operationalized to narrower tasks within which we present the theory and practice of the helixes; triple and quadruple helix models with a focus on the roles that universities play in these models. As a conclusion of the paper, we point out that universities are facing numerous challenges and changes, and the applied knowledge incorporated in the society's progress is gaining importance. In this process, it is imperative that the market serve the society, not the other way around. Otherwise, the universities will lose their autonomy and will become merely service-oriented institutions, rather than the critics of the society.